Digital Transformation as a Strategy for Improving the Management of the Nuri Sewing and Embroidery Course and Training Institution in Sukamaju Village, Sail District, Pekanbaru City - Khairiyah Desyani; Fadly Azhar; Azhar Azhar (FKIP - Universitas Riau, 2026)
This study aims to describe and analyze the implementation of digital transformation as a management improvement strategy at the Nuri Training and Education Institution (LKP) in Sukamaju Village, Sail District, Pekanbaru City. The research method used is a qualitative approach with a case study design. Data were obtained through in-depth interviews, observations, and documentation of leaders, instructors, administrative staff, course participants, and external parties such as the Pekanbaru City Education Office. Data analysis was carried out through a process of reduction, presentation, and conclusion drawing, while data validity was tested through source triangulation and member checking. The results showed that digital transformation at LKP Nuri had been implemented gradually through the application of an online registration system, Google Workspace-based digital administration, promotion through social media and websites, and the use of a cashless payment system. This transformation has had a positive impact on increasing efficiency, transparency, participant reach, and the institution's image. However, the process still faces obstacles in the form of limited technological infrastructure, uneven digital literacy, and a lack of funding support for the development of a more extensive digital system.